Options, futures, and exotic derivatives - E. Briys
Over the past two decades, the mathematically complex models of finance theory have had a direct and wide-ranging influence on finance practice. Nowhere is this conjoining of intrinsic intellectual interest with extrinsic application better exemplified than in derivative-security pricing. The backgrounds of the authors of Options, Futures and Exotic Derivatives fit perfectly this pattern of combining theory and practice and so does their book. The range and depth of subject matter show excellent taste for what is essential to know the field and what is relevant and important to its application in the financial world